Herbal medicine for the treatment of chronic rhinosinusitis: A systematic review and meta-analysis - Lee, Boram; Kwon, Chan-Young; Park, Man Young (Frontiers in Pharmacology, 2022)
Objectives: Chronic rhinosinusitis (CRS) is a disease with a high prevalence and a high socioeconomic burden. This study aimed to conduct a comprehensive systematic review to update the evidence on the use of herbal medicine (HM) for CRS treatment. Methods: A total of 14 electronic databases for randomized controlled trials (RCTs) evaluating the effects of HM on the treatment of CRS were searched for articles published before July 2021. The primary outcome was CRS severity post-treatment, measured with the Visual Analogue Scale (VAS) and Total Effective Rate (TER). The risk of bias of the included studies and the quality of evidence of the main findings were assessed using the Cochrane Collaboration’s risk of bias tool and the Grading of Recommendations, Assessment, Development, and Evaluations tool. Results: A total of 80 RCTs were included. Compared to placebo, HM significantly improved CRS severity as measured by TER and VAS. When HM was compared with conventional treatment (CT) as monotherapy or adjuvant therapy, CRS severity measured by TER and VAS, quality of life, Lund-Kennedy endoscopy score, Lund-Mackay computed tomography score, and nasal mucociliary function were significantly improved in the HM group. No serious adverse events associated with HM were reported. The risk of bias was generally unclear, and the quality of evidence ranged from moderate to low. Conclusions: This review found some limited clinical evidence that HM or HM combined with CT may be more effective and safer than CT alone in treating CRS. However, the methodological quality of the included studies was generally low, and the quality of the evidence needs to be improved.